1-Aminomethyl SAR in a novel series of flavagline-inspired eIF4A inhibitors: Effects of amine substitution on cell potency and in vitro PK properties. (1st September 2021) - Nilewski, Christian; Michels, Theodore D.; Packard, Garrick K.; Xiang, Alan X.; Sprengeler, Paul A.; Eam, Boreth; Fish, Sarah; Thompson, Peggy A.; Wegerski, Christopher J.; Nevarez, Andres; Clarine, Jeff; Sperry, Samuel; et al.
Graphical abstract: Abstract: Flavaglines such as silvestrol (1 ) and rocaglamide (2 ) constitute an interesting class of natural products with promising anticancer activities. Their mode of action is based on inhibition of eukaryotic initiation factor 4A (eIF4A) dependent translation through formation of a stable ternary complex with eIF4A and mRNA, thus blocking ribosome scanning. Herein we describe initial SAR studies in a novel series of 1-aminomethyl substituted flavagline-inspired eIF4A inhibitors. We discovered that a variety of N -substitutions at the 1-aminomethyl group are tolerated, making this position pertinent for property and ADME profile tuning. The findings presented herein are relevant to future drug design efforts towards novel eIF4A inhibitors with drug-like properties.